Intradural Staphylococcus aureus Abscess of the Cauda Equina in an Otherwise Healthy Patient - Thomas J. Sorenson; Giuseppe Lanzino (Case Reports in Surgery)
Abscesses involving the spine are usually located in the epidural space. In rare circumstances, intradural spinal abscesses can occur, typically in the setting of tuberculosis or other predisposing systemic conditions. In this illustrated case report, we discuss the imaging and intraoperative findings of an otherwise healthy patient with an intradural abscess of the cauda equina caused by Staphylococcus aureus. Although rare, intradural spinal abscesses can occur in the absence of typical “red flags” for infection, and a bacterial abscess should be considered in the differential diagnosis of intradural spinal cystic enhancing lesions.